PENGARUH FAKTOR PENENTU MINAT DAN KEPUTUSAN SISWA DALAM MEMILIH SEKOLAH DI SMK NEGERI 1 PEUREULAK - Mardiana, Mardiana; Mariyudi, Mariyudi; Rusydi, Rusydi (J-MIND (Jurnal Manajemen Indonesia), 2021)
This research aims to analyze the influence of servant leadership and communication competence on the facilitators performance of PKH in north Aceh with job satisfaction as the intervening variables. Sampling using the census method with total sample of 150 PKH facilitators in North Aceh. The tool analysis used is Structural Equation Modeling (SEM) with using AMOS. The results of this research show that servant leadership positively influences, but not significantly on job satisfaction and performance. Communication competence significantly and positively influences on satisfaction and performance. Job satisfaction significantly and positively influences on performance. Job satisfaction does not mediate the relationship servant leadership toward performance. Job satisfaction partially mediates the influence of communication competence toward performance.